Distributed MAS with Leaderless Consensus to Job-Shop Scheduler in a Virtual Smart Factory with Modular Conveyors - de Sousa, Alex Luiz; de Oliveira, André (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
Increasingly intelligent and adaptable manufacturing systems are required to meet the current demands for customization and more excellent responsiveness in the factories. Multi-agent technology can be used to make these systems compatible with Industry 4.0 concepts, integrating elements of the factory that communicate and collaborate continuously, resulting in a more optimized and self-organized production. This article presents a distributed Multiagent System (MAS) that interacts with elements of a virtual Smart Factory, developing behaviors to control the production and logistics of modular conveyors at the factory. A Job Shop Scheduling algorithm, supported by a leaderless consensus mechanism, allows the execution of tasks with diﬀerent processing orders. The system can pre-adjust its transport route to pass certain groups of machines in the required order.